THE EFFECT OF BRASSICA OLERACEA SEEDS EXTRACTS ON SOME PATHOGENIC BACTERIA - Majeed, Majid; Farhan, Hussain (Iraqi Journal of Science, 2024)
The antibacterial effect of (Brassica oleracea) Methanolic and aqueous crud extract was evaluated by an in vitro study testing the growth of various Gram-Positive and Gram-Negative bacteria . The bactericidal activity of this extracts was analyzed by serial dilution in tubes.In same time,the qualitative chemical tests was done for determine active materials in seeds of plant.This study,found that Gram-Negative and Gram-Positive bacteria susceptible to very low Methanolic extract concentrations. On the other hand, Gram-positive bacteria were more susceptible than Gram-negative bacteria, the minimal bactericidal concentration of Gram-positive bacteria was( 8 mg/100 ml) but minimal bactericidal concentration of Gram-negative bacteria was (16 mg/100 ml) that mean duble inhibation concentration of Gram-positive bacteria .but in same time ,not susceptible to aqueous extract.The chemical Test for crude Methanolic Extracts Indicate the Existance of: Glycosides , Alkaloid , Saponine , Essintial oils , Flavonoid and Terpines .this study suggest that Methanolic extract of ( Brassica olercea) seeds have inhibation effect on Gram-Posative and Gram-Negative bacteria